Psychological Well-being of Health Workers in Fatumnasi Public Health Center - Nubatonis, Aseptiany Marsanti; Berek, Noorce Christine; Damayanti, Yeni; Kiling, Indra Yohanes (Journal of Health and Behavioral Science, 2024)
Abstract. This research aims to see the description of the psychological well-being of health workers at the Fatumnasi Health Center using a photovoice approach with thematic analysis. This research is important to do because there has been no research at this Health Center that reveals psychological well-being from the perspective of workers at Fatumnasi Heatlh Center. This research uses the theory of psychological well-being from Ryff (1989) which includes six dimensions of psychological well-being, namely self acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. This research involved 8 health workers working at the Fatumnasi Health Center, who were selected using a purposive sampling technique where participants must meet the criteria to describe psychological well-being from the perspective of health workers. The results of the analysis show a description of psychological well-being related to the following four themes: self-acceptance, mastery of confusion, autonomy, and the hopes of a health worker. Keywords: Psychological well-being, health workers, public health center